Persian Illuminationism as a Heuristic Methodology in Creative Practice-led Research - Najafi, Hossein (Revista GEMInIS, 2022)
This article is structured into two parts. The first considers the research paradigm that emanates from Persian Illuminationism (especially the works the Persian philosopher Suhrawardi). His illuminationist way of knowing, ‘knowledge by presence’, has enabled many artists to approach the inquiry through a relationship between intuition and praxis. The second section of the article is concerned with methodology, and I explain how illuminationism is consolidated through a heuristic inquiry. I posit a journey that comprises seven stages of self-realisation drawn from The Conference of the Birds (a classical illuminationist Persian text by Attar of Nishapur). These stages correlate somewhat with Moustakas’ (1990) seven essential concepts of heuristic inquiry. However, I argue that where Moustakas’ concepts eventually focus on meeting the requirements of producing research outcomes, Attar’s illuminationist framework preserves the openness of inquiry and may facilitate ongoing discovery.).